Foreign Technology Transfer in China - Slezáková, Lucie (2023)
The thesis explores foreign technology transfer in China, with a focus on the role of FDI in facilitating the process. FDI is essential for economic growth and brings in new technologies, managerial expertise, and financial resources that stimulate innovation and productivity. As China becomes an important player in innovation, foreign investors seek access to its markets. The thesis analyses China's policies related to FDI and technology transfer and their effectiveness. It also provides an overview of technology transfer indicators, identifying trends, challenges, and opportunities associated with FDI-driven technology transfer in China. The research questions are: How has FDI contributed to technology transfer and innovation in China? What are the policy implications for China's future development? The hypothesis suggest that while China's criticized forced technology transfer practices may have negative impacts, the evidence should also reveal benefits of FDI for China's innovation. The thesis uses qualitative and quantitative methods to examine the relationship between FDI, technology transfer, and innovation in China.